Assessment of autozygosity in Nellore cows (Bos indicus) through high-density SNP genotypes - Zavarez, Ludmilla B.; Utsunomiya, Yuri T.; Carmo, Adriana S.; Neves, Haroldo H. R.; Carvalheiro, Roberto; Ferenčaković, Maja; Pérez O'Brien, Ana M.; Curik, Ino; Cole, John B.; Van Tassell, Curtis P.; da Silva, Marcos V. G. B.; Sonstegard, Tad S.; et al. (Frontiers in Genetics, 2015)
The use of relatively low numbers of sires in cattle breeding programs, particularly on those for carcass and weight traits in Nellore beef cattle (Bos indicus) in Brazil, has always raised concerns about inbreeding, which affects conservation of genetic resources and sustainability of this breed. Here, we investigated the distribution of autozygosity levels based on runs of homozygosity (ROH) in a sample of 1,278 Nellore cows, genotyped for over 777,000 SNPs. We found ROH segments larger than 10 Mb in over 70% of the samples, representing signatures most likely related to the recent massive use of few sires. However, the average genome coverage by ROH (> 1 Mb) was lower than previously reported for other cattle breeds (4.58%). In spite of 99.98% of the SNPs being included within a ROH in at least one individual, only 19.37% of the markers were encompassed by common ROH, suggesting that the ongoing selection for weight, carcass and reproductive traits in this population is too recent to have produced selection signatures in the form of ROH. Three short-range highly prevalent ROH autosomal hotspots (occurring in over 50% of the samples) were observed, indicating candidate regions most likely under selection since before the foundation of Brazilian Nellore cattle. The putative signatures of selection on chromosomes 4, 7 and 12 may be involved in resistance to infectious diseases and fertility, and should be subject of future investigation.